Egg and Dietary Cholesterol Intake and Risk of All-Cause, Cardiovascular, and Cancer Mortality: A Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies - Darooghegi Mofrad, Manije; Naghshi, Sina; Lotfi, Keyhan; Beyene, Joseph; Hypponen, Elina; Pirouzi, Aliyar; Sadeghi, Omid (Frontiers in Nutrition, 2022)
Objective This systematic review and meta-analysis of prospective cohort studies examined the associations between egg and dietary cholesterol intake and the risk of mortality from all causes, including cardiovascular disease (CVD) and cancer. Methods We searched PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until April 2021, as well as references to the relevant articles retrieved. Random-effects models were used to calculate summary relative risk (RR) and 95% confidence intervals (CIs) for the highest vs. lowest categories of egg and dietary cholesterol intake. Also, linear and non-linear dose–response analyses were conducted to examine the dose-response relationships. Results We included 55 studies, comprising data from 2,772,486 individuals with 228,425, 71,745, and 67,211 cases of all-cause, CVD, and cancer mortality, respectively. Intake of each additional egg per day was associated with a 7% higher risk of all-cause (1.07, 95% CI: 1.02–1.12, I2 = 84.8%) and a 13% higher risk of cancer mortality (1.13, 95% CI: 1.06–1.20, I2 = 54.2%), but was not associated with CVD mortality (1.00, 95% CI: 0.92–1.09, I2 = 81.5%). Non-linear analyses showed increased risks for egg consumption of more than 1.5 and 0.5 eggs/day, respectively. Each 100 mg/day increment in dietary cholesterol intake was associated with a 6% higher risk of all-cause mortality (1.06, 95% CI: 1.03–1.08, I2 = 34.5%) and a 6% higher risk of cancer mortality (1.06, 95% CI: 1.05–1.07, I2 = 0%), but was not associated with CVD mortality (1.04, 95% CI: 0.99–1.10, I2 = 85.9%). Non-linear analyses demonstrated elevated risks of CVD and cancer mortality for intakes more than 450 and 250 mg/day, respectively. Conclusions and Relevance High-dietary intake of eggs and cholesterol was associated with all-cause and cancer mortality. Little evidence for elevated risks was seen for intakes below 0.5 egg/day or 250 mg/day of dietary cholesterol. Our findings should be considered with caution because of small risk estimates and moderate between-study heterogeneity. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=252564, PROSPERO, identifier: CRD42021252564.